2019
DOI: 10.1002/kjm2.12117
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of DMBT1 in cervical squamous cell carcinoma

Abstract: To explore the possible influence of deleted in malignant brain tumor 1 (DMBT1) in cervical squamous cell carcinoma (CSCC). DMBT1 expression was detected by Real‐time reverse transcription PCR (qRT‐PCR) and immunohistochemistry in CSCC and adjacent normal tissues from 167 CSCC patients, and its relationship with clinicopathological features and prognosis was analyzed. Besides, the in vitro experiments, including MTT, Cell‐Light EdU, Wound‐healing, Transwell invasion, Annexin V‐FITC/PI staining, qRT‐PCR, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…In the present report we showed that DMBT1 expression levels were down regulated in cervical cancer tissues and its low expression was associated with poor prognosis and dismal outcome. Similar results were found by previous studies (14). Zhang (14) showed that mRNA and tissue protein DMBT1 levels were downregulated in cervical cancer tissues in comparison to normal cervical mucosa.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present report we showed that DMBT1 expression levels were down regulated in cervical cancer tissues and its low expression was associated with poor prognosis and dismal outcome. Similar results were found by previous studies (14). Zhang (14) showed that mRNA and tissue protein DMBT1 levels were downregulated in cervical cancer tissues in comparison to normal cervical mucosa.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found by previous studies (14). Zhang (14) showed that mRNA and tissue protein DMBT1 levels were downregulated in cervical cancer tissues in comparison to normal cervical mucosa. These findings collectively showed DMBT1 tumor suppressor role in cervical cancer.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations